Students’ Perception of Using Google Classroom for EFL Learning - Subari, Imam (STKIP PGRI Bandar Lampung, 2022)
One of the most used E-Learning platforms is Google Classroom. Google develops Google Classroom for academic purposes that support an online learning platform. This research was conducted to investigate students’ perception of using google classroom for EFL learning in STKIP PGRI Bandar Lampung during the COVID-19 pandemic. This study used a questionnaire as a research instrument to collect the data. The researcher conducted the reliability and validity test before using this questionnaire. The students answered the questionnaire through the online method. The questionnaire was responded to by 30 undergraduate students in STKIP PGRI Bandar Lampung who learned English courses using Google Classroom during the covid-19 pandemic. The questionnaire was analyzed used by the researchers using SPSS version 25. This study showed that Google Classroom could be used in e-learning, especially during the COVID-19 pandemic. Google Classroom is suitable for conducting learning activities, especially for teaching EFL learners. Google Classroom can improve students’ communication and enrich learning activities' content and material. Google Classroom can fit with the necessity of EFL students in STKIP PGRI Bandar Lampung. Therefore, the students feel that Google Classroom can make their job easier as students, improve the student's self-learning, and enhance the communication between the students and the teachers.